Successful Treatment of Atopic Dermatitis with Dupilumab in a Patient with Non-Hodgkin's Lymphoma - YunMi Qiu; Kamran Ali; HaiYue Lou; JingPeng Shan; Liming Wu (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)